Hygiene aspect of treating human urine by alkaline dehydration. (1st November 2018) - Senecal, Jenna; Nordin, Annika; Simha, Prithvi; Vinnerås, Björn
Abstract: Over four billion people are discharging untreated human excreta into the environment without any prior treatment, causing eutrophication and spreading disease. The most nutrient rich fraction is the urine. Urine can be collected separately and dehydrated in an alkaline bed producing a nutrient rich fertiliser. However, faecal cross-contamination during the collection risks to introduce pathogens to the urine. The objective of this hygiene assessment was to study the inactivation of five microorganisms ( Ascaris suum, Enterococcus faecalis, bacteriophages MS2 and ΦX 174 and Salmonella spp) in alkaline dehydrated urine. Fresh human urine was dehydrated in wood ash at 42 °C until the pH decreased to ≤10.5, at which point the saturated ash was inoculated with faeces containing the microorganisms and left open to the air (mimicking stockpiling of the end product) at temperatures of 20 and 42 °C. The bacteria and bacteriophages were inactivated to below the detection limit (100 cfu ml −1 for bacteria; 10 pfu mL −1 for bacteriophages) within four days storage at 20 °C. A. suum inactivation data was fitted to a non-linear regression model, which estimated a required 325 days of storage at 20 °C and 9.2 days at 42 °C to reach a 3 log10 reduction. However, the urine dehydration in itself achieved a concentration <1 A . suum per 4 g of dehydrated medium which fulfil the WHO guidelines for unrestricted use.